Intermetallic Cu3Sn Phase Layer on Electrode’s Tip of Galvanized Resistance Spot Welding - Anis, Muhammad; Irsyadi, Aulia; Ferdian, Deni (UI Scholars Hub, 2009)
Intermetallic Cu3Sn Phase Layer on Electrode’s Tip of Galvanized Resistance Spot Welding. A resistance spot welding method is commonly used in automotive industries application. In a resistance spot welding method, the copper electrode has a significant role as an electric current carrier for joining thin metal sheet. This research was focused on studying the effect of tin layer at the electrode tip for joining galvanized steel sheet. The main variable of this research is in the thickness of the intermetallic Cu3Sn layer. The result showed that the introduction of tin layer less than 1 μm in thickness on the electrode tip gives a comparable shear strength and nugget diameter distribution with the unplated electrode tip.